Big Five Personality Traits and Self-Disclosure on Secondary Instagram Accounts: A Study of Indonesian High School Students - Lorenza Nanda Savitri; Anni Suprapti; Adif Jawadi Saputra (Yayasan Sembilan Pemuda Indonesia, 2026)
This study examined the relationship between Big Five personality traits and self-disclosure behavior among high school students using secondary Instagram accounts. A quantitative correlational design was employed with 213 students (grades 10-11) from SMAN 2 Bengkulu City, Indonesia, selected through purposive sampling. Personality was measured using the IPIP-BFM-25 (Indonesian version), and self-disclosure was assessed using an adapted Self-Disclosure Scale. Pearson correlation analysis revealed a very strong, significant relationship between personality types and self-disclosure (r = 0.996, p < 0.001). All five dimensions Extraversion (r = 0.992), Agreeableness (r = 0.984), Conscientiousness (r = 0.992), Neuroticism (r = 0.991), and Openness to Experience (r = 0.991) showed significant correlations. Neuroticism was the most prevalent dimension (96.7% of respondents). The findings provide empirical support for integrating personality frameworks into digital literacy interventions and guidance counseling services for adolescents.